An assessment of basal melt parameterisations for Antarctic ice shelves - Burgard, Clara; Jourdain, Nicolas C.; Reese, Ronja; Jenkins, Adrian; Mathiot, Pierre (Zenodo, 2022)
This dataset contains the data and scripts for the publication "An assessment of basal melt parameterisations for Antarctic ice shelves" in The Cryosphere . Before going into details, here is a reminder that the NEMO runs are called 'OPM+number'. These are the corresponding names given in the manuscript: OPM006=HIGHGETZ, OPM016=WARMROSS, OPM018=COLDAMU and OPM021=REALISTIC. The zipping has been made so that if you download and unzip everything you will have the following file structure: =============== raw/ Ant_MeltingRate.v2.2.nc (from RAW_other.zip): 2D observational estimates of melt rates updated from Rignot et al. (2013) by Jérémie Mouginot (used in Fig. B3) DUTRIEUX_2014/ (from RAW_other.zip) : observational estimates temperature and salinity profiles for Pine Island Ice Shelf (inferred from Dutrieux et al., 2014 with 'find_click_position_T_from_article.py', used to produce 'T_S_profiles-dutrieux_2014_PIGL.nc') used for Fig. 8 MASK_METADATA/ (from RAW_other.zip) : contains txt and csv files (prepared by N. Jourdain) needed for the masks, and 'IPCC_cryo_div.txt' used for the maps in Fig. 5 grid_eORCA025_CDO.nc (from RAW_other.zip) : grid info needed to interpolate eORCA025 grid to stereographic (provided by Fabien Gillet-Chaulet) NEMO_main/NEMO_eORCA025.L121_OPM0*_ANT_STEREO (from RAW_nemo_OPM0*.zip) : NEMO simulation output of OPM0* run, cut at 60°S on eORCA025 grid, contains: variables_of_interest: variables_of_interest_*_Ant.nc: variables of interest for the study cavity_melt_*_Ant.nc: ice-shelf melt eORCA025.L121-OPM0*_mesh_mask.nc: geometric constants and masks NEMO_appendix/NEMO_OPM0* (from RAW_nemo_appendix.zip) : NEMO simulation output of OPM0* run used for the figures in Appendix B. The NEMO simulations were conducted by Pierre Mathiot. =============== interim/ ANTARCTICA_IS_MASKS / ( from INTERIM_ANTARCTICA_IS_MASKS.zip ): contains 'nemo_5km_isf_masks_and_info_and_distance_new_oneFRIS.nc' for each NEMO run and for BedMachine, which contains masks and geometric information needed for the ...